Effect of Training on manual reaching behavior in infants - Integrative Review of Clinical Trials - Guimarães, Elaine Leonezi; Rodrigues, Nathália Raissa Silva; Affonso, Giovanna; Loss, Igor de Oliveira (Seven Editora, 2023)
This review was designed to seek evidence for clinical practice on training infants to manual reaching. For its execution, six stages were covered: 1) identification of the theme and elaboration of the research question; 2) establishment of inclusion criteria; 3) definition of the information to be extracted; 4) evaluation of studies; 5) interpretation of results; 6) synthesis of knowledge. The databases used were: National Library of Medicine, Literatura Latino-Americana e do Caribe em Ciências da Saúde, Medical Literature Analysis, Biblioteca Virtual em Saúde, Scientific Electronic Library Online, Science Direct, Pan American Health Organization, COCHRANE Library. Evidences indicate that the training provides fundamental experiences for the improvement of motor behavior, and should be used in clinical practice by parents and/or caregivers. DOI:https://doi.org/10.56238/alookdevelopv1-108